Afrodescendant population in Guerrero: representation and appropriation of racial stereotypes - Alcocer Perulero, Marisol (Cultura y Representaciones Sociales, 2019)
This paper aims to explore —through a qualitative analysis that resorts to interview and recovers some elements of microanalysis— the way in which the Afrodescendant population in general has been historically represented, in particular on the Costa Chica region of the state of Guerrero, Mexico. At the same time, it reflects on the way in which members of three communities of the municipality with the largest population that self-define themselves as Afrodescendant and retake, or not, some of the elements of that stereotyped representation in order to relate to other ethnic groups. The communities are Cuajinicuilapa, head municipality, San Nicolás and El Pitahayo. The Afrodescendant population has been designated through a historical process marked by coloniality, due to a stereotyped and hierarchical vision; at the same time, it is found that the population deploys a series of constructions of meanings and discourses to define itself in certain contexts. Therefore, people react to such designations, they reappropriate these stereotyped constructions and use them to perform representations before other ethnic groups —mestizos or indigenous— while reproducing the stereotyped discourses. The paper focuses on the stereotypes that Afro-Mexicans build about their women in particular.